Peningkatan Kompetensi Guru Melalui Pelatihan Penggunaan Artificial Intelligence (AI) di SMA Negeri 5 Medan - Dharmawati Dharmawati; Nur Wulan; Divi Handoko; Sarudin Sarudin; Suriati Suriati; Sumi Khairani; Liza Fitriana (Unity Academy, 2025)
The digital era has made artificial intelligence (AI) technology an increasingly important tool in various fields, including education. For high school (SMA) teachers, AI offers great opportunities to improve teaching effectiveness, reduce administrative workload, and create more personal and innovative learning experiences. This Community Service Activity (PKM) is motivated by the lack of teacher competence in creating AI-based learning media. This problem is caused by teachers only having basic skills in using AI, and the majority of teachers experiencing this difficulty are senior teachers born in the 1960s. The objective of this activity is to improve teachers' competence in using AI technology to create teaching materials to support the learning process. The activity is carried out with a combination of lecture and practice methods. The contribution of this activity lies in empowering teachers to independently produce digital teaching media. The evaluation results show that 95% of participants successfully created at least one digital teaching media, 75% of teachers were able to create two or more different designs. These evaluation results indicate that this community service activity is effective in improving the competence of teachers at SMA Negeri 5 Medan.